PERANCANGAN LABORATORIUM CAMPURAN HRS-WC DENGAN PENGGUNAAN BUTON GRANULAR ASPHALT (BGA) SEBAGAI BAHAN ADDITIVE - Howardy, Howardy; Suparma, Latif Budi; Satyarno, Iman (Civil Engineering Forum Teknik Sipil, 2008)
Increasing demand for asphalt in the country results in 650,000 tons of imported asphalt per year. The early damage of asphalt pavement is due to increasing axle loads and high temperature climates. On the other side, natural asphalt in Buton island of Sulawesi Tenggara, which is the biggest natural asphalt deposit district in world containing about 677 million tons of asphalt, has not been optimally exploited. This research designs HRS-WC mixture by utilizing Buton Granular Asphalt ( BGA), one of Buton asphalt form, as additive in the binder. The objective of this research is to identify mixture characteristics by referring to Marshall characteristic. Mixture is designed under the Marshall Standard procedure and 24 hours Marshall Immersion at optimum binder content according to Indonesian specification (Bina Marga, 2005) for Hot Rolled Sheet-Wearing Course ( HRS-WC). Mixture design applies the additive BGA (Buton Granular Asphalt) variations of 0%, 2%, 4%, 6%, 8% and 10% to the total mixture. The results of the research showed the optimum asphalt content of specimen Buton Granular Asphalt (BGA) variations of 0%, 2%, 4%, 6%, 8%, and 10% were 8.3%, 7.7%, 7.2%, 6.7%, 6.4%, and 6.3%, respectively. The misture reached the Stability values at 1373.8 kgs, 1554.9 kgs, 1493.1 kgs, 1419.3 kgs, 1230.0 kgs, and 1429.3 kgs, respectively. Index of retained strength obtained were 98.1%, 75.4%, 87.9%, 93.0%, 98.6%, and 80.5%, respectively. Composition suitable for addition Buton Granular Asphalt (BGA) at HRS-WC mixture were 2% and 4% BGA, with the mixture density values of 2.266 gr/cm3 and 2.218 gr/cm3, mixture VMA values of 19.9% and 18.9%, mixture VFWA values of 74.7% and 71.4%, mixture VITM values of 5.0% and 5.4%, mixture Stability values of 1554,9 kgs and 1493,1 kgs, mixture flow value of both of 3,0 mm, mixture MQ values of524.1 kg/mm and 493.1 kg/mm, mixture Index of retained strength of 75.4% and 87.9%.